Light response of Vibrio parahaemolyticus - Kuroyanagi, Yunato; Tsuchiya, Jiro; Jiang, Chunqi; Mino, Sayaka; Kasai, Hisae; Motooka, Daisuke; Iida, Tetsuya; Satomi, Masataka; Sawabe, Tomoo (Frontiers in Marine Science, 2022)
Light is one of the most critical stimuli in the majority of living organisms. In the last two decades, blue light (BL) has become a major subject of attention because of developments in light-emitting diodes (LED). The effects of BL on eukaryotic organisms and phototrophic prokaryotes have been well studied, but the knowledge of its effects on non-phototrophic prokaryotes remains unclear. Since BL can penetrate seawater, it is expected that most prokaryotes living in the ocean possess molecular mechanisms which protect against BL. The aim of this study is to assess the molecular mechanisms of Vibrio parahaemolyticus cells against BL as a marine bacterial model compared to other wavelength light exposures. Physiological and transcriptomic analyses of BL-exposed cells compared to other light treated cells revealed the highest ROS fold change, the highest number of differentially expressed genes (DEGs), and up-regulation in the gene responsible to not only compatible solute such as glycine betaine and ectoine but also iron-sulfur biosynthesis related to ROS formation. Furthermore, red light (RL) up-regulated the expression of cryptochrome DASH, a protein known to be excited by BL, and orange light (OL) decreased the expression of thermostable direct hemolysin (TDH), suggesting that OL attenuates the virulence of V. parahaemolyticus. In addition, the expression of VtrA (V. parahaemolyticus type III secretion system 2 (T3SS2) regulator A) but not VtrB (V. parahaemolyticus T3SS2 regulator B) increased under both light treatments, indicating that light exposure is unlikely to be involved in T3SS2-mediated pathogenicity. These results expand our knowledge on unique light responses in non-phototrophic marine prokaryotes.